Effects of Atorvastatin on Oxidative Stress Biomarkers and Mitochondrial Morphofunctionality in Hyperfibrinogenemia-Induced Atherogenesis. (22nd October 2014) - Scribano, María de la Paz; Baez, María del Carmen; Florencia, Becerra; Tarán, Mariana Denise; Franco, Signorini; Balceda, Ariel G.; Moya, Mónica
Abstract : Relationship between hyperfibrinogenemia (HF), oxidative stress, and atherogenesis was established. Effect of atorvastatin (Ator) was assessed. Wistar male (6 months) rats were studied: Ctr, control, without HF induction; Ctr-Ator, without HF treated with atorvastatin; AI, atherogenesis induced, and AI-Ator, atherogenesis induced and treated with atorvastatin. Atherogenesis was induced by daily adrenaline injection (0.1 mL/day/rat) for 90 days; treatment started 15 days after induction. Fibrinogen (mg/dL) and nitric oxide (NO) were measured in plasma (mM) and superoxide dismutase (SOD) (U/mL) in red cell lysate by spectrophotometry. Slices of aorta were analyzed by electron microscopy (EM). ANOVA and chi-square test were used;P < 0 . 05 was established. There were no significant differences between Ctr and Ctr-Atorv in fibrinogen, NO, and SOD values. Comparing Ctr with AI an increase of fibrinogen is observed (P < 0 . 001 ), but it decreased after administration of atorvastatin in AI-Ator (P < 0 . 001 ). NO diminished in AI relative to Ctr and increased in AI-Ator (P < 0 . 001 ). SOD showed an increase in AI and AI-Ator compared to Ctr (P < 0 . 001 ). EM revealed expansion of intermembrane space and disorganization of crests in AI. In AI-Ator mitochondrial areas and diameters were similar to control. Atorvastatin normalizes HF, stabilizes NO, increases SOD, and produces a partial regression of mitochondrial lesions.